1999
DOI: 10.2337/diacare.22.10.1694
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between early childhood immunizations and beta-cell autoimmunity.

Abstract: The results suggest that changing the early childhood immunization schedule would not affect the risk of developing beta-cell autoimmunity or type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 2 publications
(2 reference statements)
2
29
1
4
Order By: Relevance
“…In our study, antibodies neither appeared more often after MMR vaccination nor were found more often in vaccinated children compared with offspring that were not MMR vaccinated. Also, no influence by vaccination on the development of islet autoimmunity was found in a cohort of first-degree relatives from the U.S. (14). Overall, the findings in first-degree relatives are consistent with a report from New Zealand that found no associations between year-by-year incidences of childhood diabetes and the introduction, alteration, or abandonment of vaccination programs (15).…”
Section: A B Tbesupporting
confidence: 87%
“…In our study, antibodies neither appeared more often after MMR vaccination nor were found more often in vaccinated children compared with offspring that were not MMR vaccinated. Also, no influence by vaccination on the development of islet autoimmunity was found in a cohort of first-degree relatives from the U.S. (14). Overall, the findings in first-degree relatives are consistent with a report from New Zealand that found no associations between year-by-year incidences of childhood diabetes and the introduction, alteration, or abandonment of vaccination programs (15).…”
Section: A B Tbesupporting
confidence: 87%
“…In accord with the Vaccine Safety DataLink study, several other wellcontrolled retrospective studies found that immuni-zations were not associated with an increased risk of developing type 1 diabetes. [81][82][83] Therefore, the best available evidence does not support the hypothesis that vaccines cause type 1 diabetes.…”
Section: Clinical Studies Evaluating the Relationship Between Vaccinementioning
confidence: 91%
“…7,14,15 Data from the Diabetes Autoimmunity Study also provides evidence against the notion that vaccination or timing of vaccination is associated with the development of type 1 diabetes. 16 This was a prospective study of 317 children who had a first-degree family member with type 1 diabetes. The children were monitored for the development of autoimmunity to pancreatic ␤-cells, an early precursor in the development of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%